Assessment of vascular function in complete glycaemic spectrum. (4th July 2021) - Rajendran, Rajathi; Sharma, Vivek Kumar; Nandeesha, Hanumanthappa; Ananthakrishnan, Ramesh; Vinod, Kolar Vishwanath; Subramanian, Senthil Kumar
ABSTRACT: Purpose: The present study was conceived to delineate the point of vascular dysfunction along the glycemic spectrum (normoglycemic individuals with no family history of diabetes, normoglycemic individuals with family history of diabetes, prediabetic individuals, and diabetic individuals). Materials and Methods: In this cross-sectional comparative study, we enrolled 252 participants of both gender in the age group of 30–50 years. They were classified based on their family history of diabetes and glycemic status into four groups along the glycemic spectrum as mentioned above. We measured flow-mediated dilation (FMD) from brachial artery and vascular function biomarkers such as enthothelin-1 (ET-1), von Willbrand Factor (vWF), Vascular Endothelial Growth Factor (VEGF) to assess the vascular function. The comparison of data between groups were done using One Way ANOVA/Kruskal–Wallis followed by post-hoc analysis using LSD/Mann–Whitney U Test depending on the normality of the data. Spearman correlation was done between vascular function and plasma glucose levels to identify its relationship. Linear regression was carried out to identify the factors influencing the FMD across the glycemic spectrum. Results: We observed that vascular function negatively correlated with blood glucose levels. However, endothelin-1 and vWF derangement was there even in normoglycemic first degree relatives of diabetes (FDRD) and the derangement increased in prediabetes and diabetes. Physiological dysfunction in terms of decreased flow-mediated dilation starts from prediabetes only. VEGF derangement is found only in diabetic individuals. Conclusion: Vascular dysfunction is found even in normoglycemic FDRD and the derangement increased and compounded with the advancement of disease.